Michel de Certeau and the writing of modernity - Napoli, Diana (2025)
AbstractThis contribution will first examine the elements that allow us to delineate the conceptual perimeter of modernity in the work of Michel de Certeau, emphasizing, secondly, the importance of the notion of production as elaborated by Marx. Finally, it will highlight the more properly committed aspects of his work and his reflection on modernity, showing how the “writing of modernity” —understood both in its dimension as a history of modernity and in its dimension as an analysis of the forms of writing characteristic of modernity— constitutes an operation shaped by the political exigencies of its time.